Tilianin Extracted From Dracocephalum moldavica L. Induces Intrinsic Apoptosis and Drives Inflammatory Microenvironment Response on Pharyngeal Squamous Carcinoma Cells via Regulating TLR4 Signaling Pathways - Jiang, Hailun; Zeng, Li; Dong, Xueqi; Guo, Shuilong; Xing, Jianguo; Li, Zhuorong; Liu, Rui (Frontiers in Pharmacology, 2020)
Human pharyngeal squamous cell carcinoma is highly invasive and proliferative, and exhibits an extremely low five-year survival rate due to poor understanding of the underlying pathogenic mechanisms, and lack of efficient treatment. It has been shown that the immunosuppressive microenvironment created by tumor cells impairs the immune response against tumor progression, thereby affecting the prognosis for tumor patients. Thus, to improve therapeutic efficacy, it is critical to identify novel drugs with immunoinflammatory modulatory properties to treat tumor immune evasion. Tilianin, the main ingredient of total ﬂavonoids extracted from Dracocephalum moldavica L., has multiple biological functions, including cardiovascular protective effects, anti-tumor effects, and anti-inflammatory effects. In the present study, the suppressive effects of tilianin on human pharyngeal squamous cell carcinoma were investigated and the underlying mechanisms in regulating the tumor immunosuppressive microenvironment were explored. The cytotoxicity of tilianin on FaDu cells was determined by CCK-8 and clone formation assays. Moreover, the levels of toll-like receptor 4 (TLR4) signaling transduction and apoptotic pathways were determined by immunocytochemical, biochemical, and molecular biological technologies. In addition, the maturation of dendritic cells (DCs) that were co-cultured in supernatant of FaDu cells was evaluated by flow cytometry to investigate alterations in immune system function. For mechanistic exploration, TLR4 siRNA, p38 siRNA, c-Jun N-terminal kinase (JNK) siRNA, and p65 siRNA were used as loss-of-function target evaluation of tilianin therapy. Combined, these results showed that tilianin treatment increased cytotoxicity as well as the apoptotic population of FaDu cells in a dose-dependent manner. Furthermore, tilianin treatment decreased the level of anti-apoptotic markers Bcl-2 and Bcl-xL, increased the level of apoptotic factors Bad and Bax, and stimulated cytochrome c release, caspase-3 and poly ADP ribose polymerase (PARP) activation in FaDu cells. Furthermore, our findings indicated that tilianin treatment activated TLR4/p38/JNK/NF-B signaling pathways and increased the release of inflammatory cytokines. This promoted the maturation of DCs to enhance immune system function in the tumor microenvironment. Moreover, the effects of tilianin on immune system function were abolished by TLR4 siRNA and p65 siRNA. In conclusion, these findings suggested that tilianin may be of immunotherapeutic value for inhibiting human pharyngeal squamous cell carcinoma.